الاحتراق النفسي لدى عينة من الأخصائيين العياديين بالمراكز الاستشفائية بمدينة الأغواط - يوسفي سليمة; بن حمادي فاطمة الزهراء; خديجة دعماش (My University, 2021)
This study aims at identifying the level of the Psychological Burnout for a sample of clinical specialists’ in laghouat hospital centers. In this study the descriptive method was used. The study sample is composed pf 45 clinical specialist (13 males and 32 females). They were chosen on purpose. Moreover, the measure of the psychological Burnout by Maslash, depending on the semi-Directed Interview technique for 3 clinical specialists, was applied. The data was processed by the spss version 22. Finally, the study was resulted in the following: -The clinical specialists suffer from a high level of emotional exhaustion on Maslash measure in the laghouat city hospital centers. - The clinical specialists suffer from a high level of lack of sense personal accomplishment on Maslash measure in the laghouat city hospital centers. - The clinical specialists suffer from a low level of depersonalization on Maslash measure in the laghouat city hospital centers(Psychological Burnout), (Clinical specialist), (Emotional Exhaustion), (lack of sense personal accomplishment), (Depersonalization)